Desertification Process in The North-Eastern Part of The Aravalli Mountains Fringing the Thar Desert, India - Raghav, K S (Annals of Arid Zone, 2016)
The distribution of saod dunes in space and time and nature of present drainage system in the north-eastern part of the Aravalli Mountains indicate a gradual desertification. The natural and anthropogenic causes of desertification have been discLlssed.